Hepatic artery pseudoaneurysm–the Mayo Clinic experience and literature review - Gavrancic, Tatjana; Tahir, Muhammad Waqas; Gorasevic, Marko; Dumic, Igor; Rueda Prada, Libardo; Cortes, Melissa; Chipi, Patricia; Devcic, Zlatko; Ritchie, Charles; Murawska Baptista, Aleksandra (Frontiers in Medicine, 2024)
Introduction: Hepatic artery pseudoaneurysm (HAP) is a rare, potentially life-threatening condition, associated with high mortality. We reviewed HAP etiology, clinical manifestations, management, and outcome of patients treated at Mayo Clinic.This was a retrospective chart review of patients' medical records who were diagnosed and treated for HAP at the Mayo Clinic (Florida, Minnesota, and Arizona) between September 1 st , 1998 and June 30th, 2022. We identified 27 patients with HAP and described their demographics, presenting symptoms, location of HAP, etiology, associated liver pathology, type of intervention and outcome.Results: Majority of patients with HAP were men (63%) with median age of 57 years (range: 25-87 years), and HAP was intrahepatic (85.2%) and located on the right hepatic artery (RHA) (70.4%). In 89.9% of cases, HAP was caused by hepatobiliary procedures or trauma, and only 10.1% occurred spontaneously. Presenting symptoms at the time of HAP diagnosis varied from gastrointestinal (GI) bleeding (29.6%), abdominal pain (14.81%), other non-GI bleeding (11.1%), traumatic bodily injury (11.11%), and other (14.81%). Asymptomatic and accidental HAP findings were present in 18% of cases. Malignancy was found in 52% of cases, while 26% were liver transplant recipients. Known HAP (p=0.381), HAP rupture (p=0.382), anticoagulation (p=0.856), hemorrhagic shock (p=0.25), liver cirrhosis (0.143), GI bleed (0.879), hepatobiliary abscess (p=0.079), liver transplant (p=0.738), spontaneous HAP (p=0.381) and malignancy (p=0,163) were not associated with increased mortality. Need for transfusion (p=0,021), tumor invasion (p=0,023), poral vein thrombosis (PVT) (p=0,02) and liver necrosis (p=0,02) were associated with increased mortality. The overall infection rate was 3% and overall mortality was 18.5%.Discussion: HAP often occurs after hepatobiliary surgeries, liver transplants, or trauma, but it can also arise spontaneously, albeit rarely. HAP is frequently detected incidentally during routine post-transplant screenings. While HAP is typically diagnosed after complications like rupture leading to gastrointestinal hemorrhage or shock, our study indicates that these events are not necessarily linked to increased mortality. However, factors that do correlate with a higher risk of mortality include need for blood transfusions, tumor invasion, portal vein thrombosis (PVT), and presence of liver necrosis at time of diagnosis.